Kajian Terhadap Sila Keadilan Dan Teori Keadilan Berfalsafah Libertarianisme Dari Sudut Pandang Berideologi Pancasila - Susanti, Liana Endah (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2018)
Libertarianism is a classification of philosophy which considers freedom as the main perspective that must be honored. With this assumption making libertarianism is often seen as a processed result or new ideas as a more polite cover of anarchism. Libertarianism initiates a society with a minimal state role, as a manifestation of the fulfillment of rights and the creation of justice where the distribution of resources is determined by the ability of each individual through a market mechanism. With this, it is not impossible to cause a disintegration that will adversely affect their social life. Whereas on the other hand, the government, as it has been placed by libertarians, only acts as a stabilizer to monitor and ensure that there are no violations of rights that occur, not as an opening way towards the creation of a country's goals. Deeper, libertarians oppose various regulations and rules that smell of public interest as well as taxes because they are considered another form of covert slavery. This is said because for them, besides causing obligations that must be borne by each individual, government revenues will actually hinder the development and productivity of each individual. Various speculations, new arguments and terms emerge along with the development of ideological strata that claim that libertarians are as they understand them. Thus emerging new terms such as conservative, left-right, contemporary and so forth as a form of division of the libertarian camp. Based on this, it certainly makes them have their own characteristics in the placement of rights and the application of justice.